Neuropsychological profiles of adolescents with a history of childhood trauma - Ashley-Cooper, Michaela (Department of Psychology, 2014)
Traumatic events experienced in childhood, such as physical and sexual abuse, can lead to multiple long-term effects on later cognitive functioning. Empirical research has shown that specific brain regions are affected by traumatic stress, including the hippocampus and the prefrontal cortex. It follows that the cognitive abilities subserved by these regions, including spatial navigation, new learning, and executive functioning, are negatively affected. The aim of the current study was to provide a thorough investigation of how trauma exposure and PTSD effect adolescents' cognitive functioning (looking specifically at those tasks subserved by the hippocampus and the prefrontal cortex), correcting for the methodological flaws seen in the research thus far.